The Dynamics of Male Homosocial Desire and the Deconstruction of Friendship in Harold Pinter’s Betrayal - Basitha Nashiri; Syamsuddin Ro'is; Fitria Wahyuningtyas; Arsian Muhammad Fatkhul Huda (Journal of English Language Learning, 2026)
This study analyzes Harold Pinter’s play Betrayal (1978) through the theoretical lenses of male homosocial desire, as proposed by Eve Kosofsky Sedgwick, and mimetic desire, as proposed by René Girard. The primary focus of this study is to deconstruct the friendship between Jerry and Robert, which has long been regarded as the foundation of stability but is, in reality, a complex psychological battlefield. Using descriptive qualitative methods and close reading techniques, this study reveals that the male-male relationship in the play is constructed through the exclusivity of masculine spaces and rituals that position women (Emma) as commodities of circulation to validate the status of male subjects. The findings indicate that the Betrayal in Betrayal is not an isolated romantic act but a logical consequence of mimetic competition in which Jerry and Robert mimic one another to seize dominance. Furthermore, this study demonstrates how Emma’s transformation from a passive object into an active agent who reveals the truth (truth-telling) functions as a catalyst that exposes the falsity of this homosocial system. By debunking the myth of exclusive male friendship, this study concludes that masculinity in Pinter’s plays is a fragile structure, where male-to-male loyalty is a mask for mutually destructive competitive ambitions.